DataMetProcess: An open-source package and Shiny application for the acquisition and processing of meteorological data from INMET - dos Santos, Wagner Martins; Lee, Hoi Leong; Ferraz, Edimir Xavier Leal; de Assunção Montenegro, Abelardo Antônio; de Sousa Martins, Daiane Costa; Bezerra, Alan Cézar; de França e Silva, Ênio Farias; da Silva, Thieres George Freire; de Lima, João L.M.P.; Tang, Xuguang; da Rosa Ferraz Jardim, Alexandre Maniçoba [UNESP] (Elsevier, 2025)
The acquisition and understanding of meteorological data are crucial for management in various sectors of society. Thus, the objective was to develop a package in the R programming environment to download and process data provided by Brazilian National Institute of Meteorology (INMET) and to create a free web-based tool using Shiny (interactive web apps) to simplify the use of the functions provided in the package. The DataMetProcess package was developed, offering four essential functions to extract information from the database, correct time zones, change the time scale, and calculate reference evapotranspiration according to the Penman-Monteith model. The Shiny web application developed is available in three versions: (1) the code; (2) portable; and (3) a web version. The DataMetProcess package and the developed web application are effective in processing the data provided by INMET, democratizing access to information and facilitating analysis through the interactive web application. Finally, being open-source, it can be easily adapted and used worldwide. We encourage the research community to adopt this tool and provide feedback to further refine its usability and efficiency.